Phylogeography of the Solanaceae-infecting Basidiomycota fungus Rhizoctonia solani AG-3 based on sequence analysis of two nuclear DNA loci - Ceresini, Paulo C.; Shew, H. David; James, Timothy Y.; Vilgalys, Rytas J.; Cubeta, Marc A. (Biomed Central Ltd., 2007)
Background: the soil fungus Rhizoctonia solani anastomosis group 3 (AG-3) is an important pathogen of cultivated plants in the family Solanaceae. Isolates of R. solani AG-3 are taxonomically related based on the composition of cellular fatty acids, phylogenetic analysis of nuclear ribosomal DNA (rDNA) and beta-tubulin gene sequences, and somatic hyphal interactions. Despite the close genetic relationship among isolates of R. solani AG-3, field populations from potato and tobacco exhibit comparative differences in their disease biology, dispersal ecology, host specialization, genetic diversity and population structure. However, little information is available on how field populations of R. solani AG-3 on potato and tobacco are shaped by population genetic processes. In this study, two field populations of R. solani AG-3 from potato in North Carolina (NC) and the Northern USA; and two field populations from tobacco in NC and Southern Brazil were examined using sequence analysis of two cloned regions of nuclear DNA (pP42F and pP89).Results: Populations of R. solani AG-3 from potato were genetically diverse with a high frequency of heterozygosity, while limited or no genetic diversity was observed within the highly homozygous tobacco populations from NC and Brazil. Except for one isolate (TBR24), all NC and Brazilian isolates from tobacco shared the same alleles. No alleles were shared between potato and tobacco populations of R. solani AG-3, indicating no gene flow between them. To infer historical events that influenced current geographical patterns observed for populations of R. solani AG-3 from potato, we performed an analysis of molecular variance (AMOVA) and a nested clade analysis (NCA). Population differentiation was detected for locus pP89 (Phi(ST) = 0.257, significant at P < 0.05) but not for locus pP42F (Phi(ST) = 0.034, not significant). Results based on NCA of the pP89 locus suggest that historical restricted gene flow is a plausible explanation for the geographical association of clades. Coalescent-based simulations of genealogical relationships between populations of R. solani AG-3 from potato and tobacco were used to estimate the amount and directionality of historical migration patterns in time, and the ages of mutations of populations. Low rates of historical movement of genes were observed between the potato and tobacco populations of R. solani AG-3.Conclusion: the two sisters populations of the basidiomycete fungus R. solani AG-3 from potato and tobacco represent two genetically distinct and historically divergent lineages that have probably evolved within the range of their particular related Solanaceae hosts as sympatric species.